Analysis of Creative Thinking Skills among Grade 11 Students at SMAN 14 Gowa - Nurasizha, Nurasizha; Usman, Usman; Wahyuni, A. Sri Astika; Setiawan, Trisno (Department of Physics Education, Universitas Mataram, 2025)
This study analyzes the creative thinking abilities of Grade 11 students at SMAN 14 Gowa on the topic of dynamic fluids. The researchers employed a quantitative descriptive design using a survey method. The study involved 82 students selected through purposive sampling. The researchers collected data using five validated open-ended questions, each representing an indicator of creative thinking ability: fluency, flexibility, originality, and elaboration. The results indicated that, overall, students’ creative thinking ability was categorized as fairly creative, with an average interval score of 14.7. Among the indicators, fluency showed the highest achievement (62.20%), classified as high, followed by flexibility (59%), elaboration (56%), and originality (52%), all of which fell into the moderate category. These findings suggest that students demonstrate strength in generating multiple ideas; however, further instructional support is needed to enhance their ability to produce original ideas and to develop and explain ideas systematically.